HANDWASHING WITH SOAP (HWWS) EDUCATION TO IMPROVE PERSONAL HYGINE IN ILIE VILLAGE, ULE KAREN SUBDISTRIC, BANDA ACEH - Ramadhana, Phossy Vionica; Darwis, Aryandi (ABDIMU: Jurnal Pengabdian Muhammadiyah, 2025)
Handwashing with soap (CTPS) is a simple yet very effective public health intervention in preventing the transmission of infectious diseases. The low practice of CTPS in the community is a current problem. This is caused by a lack of knowledge and awareness of the importance of personal hygiene. Therefore, it is necessary to form healthy habits from an early age, especially in children who are the learning age group. The implementation of community service activities uses the lecture method through socialization and CTPS practice through competitions. Where the target in this activity is elementary school children totaling 20 participants. The results of the activity showed that participants had active participation during the activity. This is evidenced by their participation until the end of the activity. It is hoped that more innovative methods can be used to increase community motivation in practicing CTPS in daily activities.Keywords: Washing Hands with Soap, Personal Hygiene, Elementary School